Leading with gratitude : eight leadership practices for extraordinary business results - Gostick, Adrian Robert; Elton, Chester (Harper Business, an imprint of HarperCollinsPublishers, 2020)
"In Leading with Gratitude, New York Times bestselling authors, the "apostles of appreciation" Chester Elton and Adrian Gostick introduce readers to easy ways to add more gratitude to their work environment"--